The views and opinions of Rhodes University lecturers towards isiXhosa as a language of learning and teaching (LOLT) in higher education - Nkunzi, Zintle (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
This research sought to investigate how African languages function as a communicative tool in a university where English is the medium of instruction. The study's purpose is to provide a systematic review of research that has been carried out on language attitudes towards isiXhosa as a language of learning and teaching (LoLT) in higher education. The study reveals that South African higher education institutions such as Rhodes University mostly use English as the LoLT- a language which for most lecturers is not their first/home language but helps ease communication in a multilingual community. Rhodes University is characterised by multilingualism because the university community is made up of diversity in culture, language, and educational background of the people. Previously explored language attitude studies are based on students' views and this study investigated RU lecturer views and opinions towards isiXhosa as a LoLT. The study focused on the importance and the need (if any) of isiXhosa in a multilingual higher education institution. The study reveal that language barriers are one of the difficulties, but academic cultural differences seem to play a crucial role that can impact on the learning and teaching outcomes. This can lead to negative experiences and the forming of stereotypical views. These views include how lecturers are and should be trained to teach mathematics, science, and academic studies in African languages. The SA higher education practices and language use (i.e., monolingual language policy) are one of the reasons that the implementation of indigenous languages in education policies in SA is fraught with difficulties due to several factors. Amongst the factors is the fact that indigenous languages are not yet fully developed as academic languages. The study further reveals that lecturers find it difficult to teach mathematical studies in isiXhosa because of lack of terminology in the language for academic purposes particularly at a tertiary level. Furthermore, existing literature highlights the importance of the use of code-switching which is a beneficial practice for lecturers in assisting their students who struggle with English as a LoLT at RU. The lecturer views towards isiXhosa as a LoLT at RU is not only on language barrier but also about the lack of development in the language use in spaces where only English is believed to be the best such as language for academics. The study also reveals an integration of Information Communication Technology in education and how language appears as a barrier.
Keywords: Multilingualism; Bilingualism; Language and education; Xhosa language; College teachers -- South Africa -- Makhanda Attitudes; Code switching (Linguistics)